Flexural behavior of reinforced concrete beams strengthened with ultra-high performance fiber reinforced concrete. (1st March 2017) - Al-Osta, M.A.; Isa, M.N.; Baluch, M.H.; Rahman, M.K.
Highlights: Strengthening of RC beams by UHPFRC jacketing using different configurations. Jacketing using precast panels attached by epoxy or fresh cast in a mold. Three sided jacketing resulted in high capacity enhancement but reduced ductility. Two-sided and bottom jacketing yielded strength enhancement with high ductility. FE modeling of jacketed beams captured the experimental response reasonably well. Abstract: In this study, the effectiveness and efficiency of two different techniques for strengthening of reinforced concrete (RC) beams using ultra-high performance fiber reinforced concrete (UHPFRC) was investigated i.e.; (i) by sand blasting RC beams surfaces and casting UHPFRC in-situ around the beams inside a mold and (ii) by bonding prefabricated UHPFRC strips to the RC beams using epoxy adhesive. Beams under each technique were strengthened in three different strengthening configurations; (i) bottom side strengthening (ii) two longitudinal sides strengthening (iii) three sides strengthening. Bond strength tests were carried out to ascertain the bond between normal concrete and the UHPFRC, for both sand blasting and epoxy adhesive techniques. Test results for retrofitted beams under flexure regarding various behavioral attributes such as crack propagation, stiffness and failure load indicated significant positive developments resulting from the two strengthening techniques. Beams strengthened on three sides showed the highest capacity enhancement, while beams strengthened only at the bottom side showed the least enhancement. However, there were some concerns regarding loss of ductility with increased use of UHPFRC as part of the tensile retrofit. Finite element (FE) and analytical models were developed to predict the behavior of the beam specimens. The result of the models showed good agreement with experimental results, as they were able to predict the behavior of the beams with high accuracy.